2015
DOI: 10.1177/2048872615585521
|View full text |Cite
|
Sign up to set email alerts
|

The use of discharge haemoglobin and NT-proBNP to improve short and long-term outcome prediction in patients with acute heart failure

Abstract: In AHF patients discharge anaemia is a strong predictor for short and long-term rehospitalisation, while NT-proBNP seems to be a better predictor for mortality. Discharge Hb and NT-proBNP should be assessed together in order to detect the patients with higher risk of future death and rehospitalisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
(45 reference statements)
0
11
1
Order By: Relevance
“…We found that only anemia at discharge increased all-cause mortality; however, neither anemia at admission nor discharge affected the readmission rate due to worsening of ADHF. In contrast with the results of the abovementioned study [6], discharge anemia was not associated with readmission due to ADHF in our study, and this difference in clinical outcome between the two studies may be related to several factors, such as different LVEF or ethnicity of the sample. Because both are small retrospective studies, works with larger, real-world registries or randomized trials are needed to further explore this issue.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found that only anemia at discharge increased all-cause mortality; however, neither anemia at admission nor discharge affected the readmission rate due to worsening of ADHF. In contrast with the results of the abovementioned study [6], discharge anemia was not associated with readmission due to ADHF in our study, and this difference in clinical outcome between the two studies may be related to several factors, such as different LVEF or ethnicity of the sample. Because both are small retrospective studies, works with larger, real-world registries or randomized trials are needed to further explore this issue.…”
Section: Discussioncontrasting
confidence: 99%
“…To the best of our knowledge, few studies have evaluated the clinical impact of anemia at different times during hospitalization. Stojcevski et al [6] showed that discharge Hgb was related to re-hospitalization but not mortality in patients with ADHF. Other study reported that a change in the level of Hgb during hospitalization was independently associated with clinical outcomes in ADHF [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of ADHF patients has con rmed that NT-proBNP is an independent predictor of mortality both in all-cause and cardiovascular death despite different cut points, time intervals and prognostic models [26] . More recently, Biljana Stojcevski et al reported that discharge NT-proBNP should be assessed to detect the AHF patients with higher risk of short-and long-term death [27] . Although current studies employed different cut-off values for NT-proBNP, we used quartiles for multivariate analysis, which showed that only patients with the highest plasma concentration of NT-proBNP was related to poorer in-hospital outcomes scoring 1 point in the new system.…”
Section: The Predictive Elements For Adhfmentioning
confidence: 99%
“…The causes are diverse including decreased haematopoiesis frequently related to the presence of an impaired renal function, iron deficiency and also haemodilution related to the congestive state. In a retrospective analysis of patients presenting with acute heart failure anaemia was observed both on admission and discharge in 55 to 62% of the patients (1). Discharge anaemia was associated with a marked increased risk for short (30 days) and long-term (6 months and one year) rehospitalisation.…”
Section: Acute Heart Failurementioning
confidence: 99%